A new concept and finite-element study on dental bond strength tests. Issue 10 (October 2016) - Jin, Xiao-zhuang; Homaei, Ehsan; Matinlinna, Jukka Pekka; Tsoi, James Kit Hon
Abstract: Objective: Numerous bond strength tests have been performed on dental adhesion experiments. Yet, the validity of these bond strength tests is controversial due to the name ( e.g., "shear" or "tensile") may not reflect to the true and complete stress situation, i.e., assumed uniform shear or uniaxial tensile conditions. Thus, the aim of this study was to simulate and compare the stress distribution of and between shear bond strength (SBS), tensile bond strength (TBS), mold-enclosed shear bond strength (ME-SBS) and de novo lever-induced mold-enclosed shear bond strength (LIME-SBS) tests. Methods: 3-Dimensional finite element method (FEM) was used on the dental resin-bonded surfaces ( i.e., titanium alloy, dentine and porcelain) interphased with adhesive layer (thickness 5 μm) to simulate the mechanical tests. For ME-SBS, both polycarbonate and stainless steel molds were used. For LIME-SBS, stainless steel levers and molds with lengths of 3 mm, 6 mm, 12 mm, 15 mm and 18 mm were used. The applied loads on these models were 50 N, 100 N and 200 N. Results: De novo LIME-SBS test was the most optimal configuration to evaluate "shear" bond strength of adhesive in regards to providing significantly high and uniform shear stress as well as eliminating tensile stress at the interface. The conventional SBS test created very high tensile stress at the load area, whereas the TBS created optimal tensile stress but shear stress indeed co-exist. The ME-SBS test could also eliminate some of the tensile stress. Similar stress distributions pattern appeared on the Ti-adhesive models, the dentine-adhesive models and porcelain-adhesive models. Significance: None of the bond strength tests could give purely "shear" or "tensile" bond strength, but LIME-SBS seems to be the best model to evaluate the bond strength under true "shear" mode.